2021
DOI: 10.1055/a-1551-3343
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal endoscopy capacity in Eastern Africa

Abstract: Background and study aims Limited evidence suggests that endoscopy capacity in sub-Saharan Africa is insufficient to meet the levels of gastrointestinal disease. We aimed to quantify the human and material resources for endoscopy services in eastern African countries, and to identify barriers to expanding endoscopy capacity. Patients and methods In partnership with national professional societies, digestive healthcare professionals in participating countries were invited to complete an online survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Diagnosis of EC is difficult as systems could be nonspecific Gastrointestinal reflux Disease-(GERD-) like symptoms [27]. First, remote areas of Tanzania may not be served by a regional hospital that can provide diagnostic laboratory services and radiology, compared to ORCI, which provides these services and can aid in detecting EC [28][29][30]. Second, many remote areas lack the endoscopic equipment and endoscopists that would allow for greater detection of EC independent of laboratory and radiology services [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of EC is difficult as systems could be nonspecific Gastrointestinal reflux Disease-(GERD-) like symptoms [27]. First, remote areas of Tanzania may not be served by a regional hospital that can provide diagnostic laboratory services and radiology, compared to ORCI, which provides these services and can aid in detecting EC [28][29][30]. Second, many remote areas lack the endoscopic equipment and endoscopists that would allow for greater detection of EC independent of laboratory and radiology services [30].…”
Section: Discussionmentioning
confidence: 99%
“…First, remote areas of Tanzania may not be served by a regional hospital that can provide diagnostic laboratory services and radiology, compared to ORCI, which provides these services and can aid in detecting EC [28][29][30]. Second, many remote areas lack the endoscopic equipment and endoscopists that would allow for greater detection of EC independent of laboratory and radiology services [30]. Increasing the capacity of referral hospitals to offer more advanced diagnostic laboratory and radiology services and providing greater endoscopic equipment and training would allow for earlier detection of EC., Patients with esophageal cancer in remote areas face more travel barriers (transportation costs, time) to receive a diagnosis at ORCI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey from the European Society of Gastrointestinal Endoscopy (ESGE) showed that many African countries have few gastrointestinal endoscopy centers with adequate resources and the shortage of endoscopy training, lack of national endoscopy societies, and deficiencies in equipment and basic infrastructure, as well as poor water and power supplies, are the probable reasons [9]. This is especially valid in sub-Saharan Africa [9,16,17]. Mwachiro et al [17] recently analyzed gastrointestinal endoscopy volume in Eastern sub-Saharan Africa and showed a limited endoscopy capacity to meet the burden of digestives diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially valid in sub-Saharan Africa [9,16,17]. Mwachiro et al [17] recently analyzed gastrointestinal endoscopy volume in Eastern sub-Saharan Africa and showed a limited endoscopy capacity to meet the burden of digestives diseases. An overall capacity of 0.12 endoscopists, 0.12 gastroscopes, and 0.09 colonoscopes per 100,000 inhabitants was calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Upper Gastrointestinal Endoscopy (UGIE) or Oesophago-Gastro-Duodenoscopy (OGD) is an important aspect of daily practice for gastroenterologists, gastrointestinal surgeons and others involved in the diagnosis and treatment of various gastrointestinal disorders Original Research Article [1]. It is arguably the procedure of choice in the diagnosis of mucosal-based lesions of the GI tract as it permits real-time observation of the oesophageal, gastric, and duodenal mucosae, as well as permits diagnostic sampling for further pathologic studies.…”
Section: Introductionmentioning
confidence: 99%